Perilaku Konsumen Generasi Z Dalam Pembelian Fashion Muslim Pada Marketplace Indonesia - Pipit Indrawati (Universitas Wahid Hasyim Semarang, 2022)
The global halal industry is currently experiencing rapid development, including Muslim fashion in Indonesia. The growth in the number of millennials in Indonesia is also an opportunity for the Muslim fashion sub-sector to grow. The characteristics of generation Z which are closely connected with communication technology are factors that deserve to be studied in an effort to support the development of the halal industry which has been proclaimed by the government in the Islamic Economic Masterplan. Therefore, this study aims to understand the mindset and evaluate consumer behavior related to the process of forming an interest in buying Indonesian zelenial generation Muslim fashion in the marketplace. This process involves the variables of attitudes, subjective norms, perceived usefulness, ease of use and perceived risk based on the TPB and TAM theories. A quantitative approach was used in this study by collecting 260 questionnaires from generation Z consumers.. SmartPLS is used as a structural equation modeling approach to perform the analysis. The findings of this study are that the variables of attitude, subjective norm, perceived usefulness and ease of use play an important role because they have a positive and significant effect on the purchase intention of Muslim fashion in the Indonesian millennial generation in the marketplace. Attitude has a significant positive effect of 0.298 and subjective norms have a significant positive effect of 0.386. The perceived usefulness has a positive effect, although not too big, namely 0.163 and the perceived ease of use is 0.125. Meanwhile, the perceived risk has a negative effect, although not too significant, at -0.152 on the intention to purchase because generation Z is not too worried about transacting online. The magnitude of the influence of these five variables on the intention to buy Muslim fashion is 46.2% and the rest is influenced by other variables outside of this study. Industri halal secara global saat ini mengalami perkembangan yang pesat termasuk fashion muslim di Indonesia. Pertumbuhan jumlah generasi zelenial di Indonesia juga menjadi peluang bagi subsektor fashion muslim semakin berkembang. Karakteristik generasi Z yang erat terhubung dengan teknologi komunikasi merupakan faktor yang layak dikaji dalam upaya mendukung perkembangan industri halal yang telah dicanangkan pemerintah dalam Masterplan Ekonomi Syariah. Oleh karena itu, penelitian ini bertujuan memahami pola pikir serta mengevaluasi perilaku konsumen terkait proses pembentukan minat pembelian fashion muslim generasi zelenial Indonesia di marketplace. Proses ini melibatkan variabel sikap, norma subjektif, kegunaan yang dirasakan, kemudahan penggunaan dan risiko yang dirasakan berlandaskan teori TPB dan TAM. Pendekatan kuantitatif digunakan dalam penelitian ini dengan mengumpulkan 260 kuesioner dari konsumen generasi Z. SmartPLS digunakan sebagai persamaan struktural pendekatan pemodelan untuk melakukan analisis. Penelitian ini menunjukkan variable sikap, norma subjektif, kegunaan yang dirasakan dan kemudahan penggunaan memainkan peran penting karena berpengaruh positif dan signifikan terhadap minat pembelian fashion muslim pada generasi zelenial Indonesia di marketplace. Sikap berpengaruh positif signikan sebesar 0,298 dan norma subjektif berpengaruh positif signifikan sebesar 0,386. Kegunaan yang dirasakan berpengaruh positif meskipun tak terlalu besar yaitu 0,163 dan kemudahan yang dirasakan 0,125. Sementara risiko yang dirasakan berpengaruh negatif meskipun tidak terlalu signifikan sebesar -0,152 pada minat pembelian karena generasi Z tidak terlalu khawatir bertransaksi secara online. Besarnya pengaruh kelima variabel tersebut terhadap minat beli adalah sebesar 46,2% dan selebihnya dipengaruhi oleh variabel-variabel lain diluar penelitian ini.